+0

# For what value of b will the polynomial P(x) = 4x^3 - 3x^2 + bx + 6 have the same remainder when it is divided by both x - 1 and x + 3?

0
3
2429
2

For what value of b will the polynomial P(x) = 4x^3 - 3x^2 + bx + 6 have the same remainder when it is divided by both x - 1 and x + 3?

Guest May 11, 2015

#1
+80983
+10

4x^3 - 3x^2 + bx + 6  ... we can use the Remainder Theorem, here

So, if he remainders are equal, we have

4(1)^3 - 3(1)^2 + b(1) + 6 = 4(-3)^3 - 3(-3)^2 + b(-3) + 6

4 - 3 + b = -108 - 27 - 3b   simplify

1 + b = -135 - 3b

136 = -4b

b = -34

CPhill  May 11, 2015
Sort:

#1
+80983
+10

4x^3 - 3x^2 + bx + 6  ... we can use the Remainder Theorem, here

So, if he remainders are equal, we have

4(1)^3 - 3(1)^2 + b(1) + 6 = 4(-3)^3 - 3(-3)^2 + b(-3) + 6

4 - 3 + b = -108 - 27 - 3b   simplify

1 + b = -135 - 3b

136 = -4b

b = -34

CPhill  May 11, 2015
#2
+5

thank you so much

Guest May 11, 2015

### 4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details